Role of Cardiovascular Magnetic Resonance in Native Valvular Regurgitation: A Comprehensive Review of Protocols, Grading of Severity, and Prediction of Valve Surgery - Vermes, Emmanuelle; Iacuzio, Laura; Levy, Franck; Bohbot, Yohann; Renard, Cédric; Gerber, Bernhard; Maréchaux, Sylvestre; Tribouilloy, Christophe (Frontiers in Cardiovascular Medicine, 2022)
Valvular regurgitation is common in developed countries with an increasing prevalence due to aging of the population and more accurate diagnostic imaging methods. Although echocardiography is widely used for the assessment of etiology, severity of regurgitation, ventricular remodeling and time for intervention, cardiovascular magnetic resonance (CMR) has emerged as a reliable tool for assessing accurate flow, volumetric quantification and ventricular remodeling, which are key parameters to plan the timing of intervention. Indeed, CMR is the gold standard imaging modality to assess ventricular volume, mass and function; it also allows accurate calculation of regurgitant volume and regurgitation fraction in mitral regurgitation (MR), aortic regurgitation (AR), tricuspid regurgitation (TR) and pulmonary regurgitation (PR) using direct or indirect methods and more recently 4-dimensional flow. All these methods are independent of jet morphology or concomitant regurgitation. Echocardiographic quantitative thresholds for grading valvular regurgitation severity are well-established, but do not necessarily translate well to CMR. Reference values and optimal thresholds for identifying patient with severe regurgitation by CMR are not well defined with different values reported from different centers. Despite undeniable recent progress, more research focused on prognosis value of CMR quantification of valvular regurgitation is needed. We aimed to review the current evidence and identify gaps in knowledge on CMR quantification of MR, AR, TR and PR severity to propose standardized protocol and try to clarify severity criteria and quantitative threshold to guide clinicians for an optimal management.